PEMAHAMAN AKUNTANSI PELAKU UMKM TERHADAP PENYUSUNAN LAPORAN KEUANGAN - Rachmawati, Desiana; Hidayatullah, Taufik (LPPM Universitas Bina Bangsa, 2025)
MSMEs need to keep bookkeeping and carry out financial management appropriately for business continuity. This research proves the influence of accounting understanding that MSMEs have on the preparation of financial statements. A quantitative approach was taken to test the hypothesis using primary data in the form of a questionnaire. Respondents were MSME owners at Airport X with a research sample of 52 MSME owners. The analysis uses simple linear regression with the independent variable in the form of understanding accounting and the dependent variable in the form of preparing financial statements. The research results prove that the understanding of accounting possessed by MSME actors represented by business owners has a positive influence on the preparation of financial statements with an influence size of 34.4%. An average of 31.12% of respondents did not understand accounting, followed by an average of 30.38% of respondents who did not prepare financial statements. Respondents felt that complete and routine recording of financial transactions, manifested in financial statements, was not necessary. Some respondents believe that their business makes a profit by comparing the initial capital each day with the final capital, others report the number of goods sold from employees and a small number feel there is no need to find out